Superalloys 2000 (Ninth International Symposium) 2000
DOI: 10.7449/2000/superalloys_2000_405_414
|View full text |Cite
|
Sign up to set email alerts
|

γ' Formation in a Nickel-Base Disk Superalloy

Abstract: A streamlined,physics-based kinetic model was formulated, calibrated, and validated on a nickel-base superalloy. It was designed to be simplified and streamlined, to speed up calculations and facilitate linkage to finite element modeling thermal codes. The model describes and predicts the formation of y' precipitates during the heat treatment process. Standardized experimental methods were employed to calibrate and initially validate the microstructure model. The model was then validated on an oil-quenched gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
28
0
1

Year Published

2001
2001
2023
2023

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(33 citation statements)
references
References 15 publications
3
28
0
1
Order By: Relevance
“…3. In the bulk, the M 23 C 6 carbides in the grain boundaries appear to be enriched in Cr, Mo, Co, which is consistent with observations that Co is a major component in M 23 C 6 carbides in a similar disk alloy, LSHR [11]. Towards the oxidized surface, the ME3 grain boundaries are depleted in Cr, Mo, Co and enriched in Ni relative to bulk grain boundaries as shown in Fig.…”
Section: Resultssupporting
confidence: 77%
See 1 more Smart Citation
“…3. In the bulk, the M 23 C 6 carbides in the grain boundaries appear to be enriched in Cr, Mo, Co, which is consistent with observations that Co is a major component in M 23 C 6 carbides in a similar disk alloy, LSHR [11]. Towards the oxidized surface, the ME3 grain boundaries are depleted in Cr, Mo, Co and enriched in Ni relative to bulk grain boundaries as shown in Fig.…”
Section: Resultssupporting
confidence: 77%
“…Mo-rich minor phases) within the grains that are not rich in Cr, which suggests that the carbides/borides present are mostly the more stable MC carbides and M 3 B 2 borides. For stable M 23 C 6 carbides in equilibrium, the Cr content is nearly 2.5 times greater than the bulk concentration in at.% [11]. Near the surface, Cr from M 23 C 6 carbides has diffused out to help sustain the Cr 2 O 3 scale growth, while Mo and Co accumulated underneath the external scale, within γ'-dissolution layer.…”
Section: Resultsmentioning
confidence: 96%
“…Such microstructures are usually achieved by special multi-stage heat treatments, which are generally complex and costly. Some authors have already shown that such bimodal, or even multimodal, size distributions of γ' particles can also be achieved by a series of γ' nucleation bursts during continuous cooling from the solution annealed state [15][16][17][18][19][20][21][22]. Thereby, the individual particle populations precipitate at different temperatures and from different chemical compositions of the γ matrix.…”
Section: Introductionmentioning
confidence: 99%
“…Triplicate extractions were performed in each case. Extracted phases and lattice parameters were identified using x-ray diffraction (XRD) [22].…”
Section: Experimental Characterization Of Minor Phasesmentioning
confidence: 99%